Comparing Binocular Vision Suppression on an e-Reader versus a Smartphone. - Kundart, James; Momeni-Moghadam, Hamed; Nguyen, Jessica; Hayes, John R. (Journal of Behavioral Optometry, 2012)
Purpose: Normal binocular vision is an important factor that influences visual performance. Hence, this study aims to determine the differences in binocular vision suppression when using common handheld devices compared with a hard copy control. Methods: In this experimental study, 11 subjects were asked to read the same text on a backlit smartphone, non-back-lit display e-reader, and hard copy (black text on white paper). Suppression was determined by subjective reporting using anaglyphic bar readers and glasses. The viewing distance was measured with a millimeter rule. Results: The incidence of suppression was 72.7% for the e-reader, 27.2% for the hardcopy, and 18.1% for the smart-phone. There were significant differences between the e-reader and hard copy by repeated measurement ANOVA for each reading condition. The working distance was farthest with the hard copy and closest with the smartphone. The mean working distances were significantly different by repeated measurement ANOVA with all three devices, with hard copy being read at 32.9± 3.0 cm, the e-reader at 29.9+5.3 cm, and the smartphone at 28.6±5.8 cm. Conclusions: Suppression of binocular vision is more likely on an e-reader and hard copy. This occurs despite a farther working distance than the smartphone and a closer working distance on an e-reader than a hard copy.